2011
DOI: 10.1104/pp.111.180042
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Necrosis Is a Consequence of Direct Protein-Protein Interaction between a Viral RNA-Silencing Suppressor and a Host Catalase  

Abstract: Many plant host factors are known to interact with viral proteins during pathogenesis, but how a plant virus induces a specific disease symptom still needs further research. A lily strain of Cucumber mosaic virus (CMV-HL) can induce discrete necrotic spots on infected Arabidopsis (Arabidopsis thaliana) plants; other CMV strains can induce similar spots, but they are not as distinct as those induced by CMV-HL. The CMV 2b protein (2b), a known RNA-silencing suppressor, is involved in viral movement and symptom i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 38 publications
5
97
1
1
Order By: Relevance
“…Interestingly, it has also been shown that the cucumber mosaic virus (CMV) 2b protein interferes directly with plant catalase activity to induce PCD, which appears to promote CMV infection (Inaba et al, 2011). Similar to the 2b protein, we show that PsCRN63 induces PCD by promoting H 2 O 2 accumulation.…”
Section: Discussionmentioning
confidence: 50%
“…Interestingly, it has also been shown that the cucumber mosaic virus (CMV) 2b protein interferes directly with plant catalase activity to induce PCD, which appears to promote CMV infection (Inaba et al, 2011). Similar to the 2b protein, we show that PsCRN63 induces PCD by promoting H 2 O 2 accumulation.…”
Section: Discussionmentioning
confidence: 50%
“…Recent studies of gene expression profiles in various pathosystems have shown that sets of defense-related genes are expressed upon the infection of susceptible plants with several different viruses (3,4), suggesting that even susceptible plants recognize virus infection and mount defense responses. The discovery of coordinated induction of defense-related genes in compatible plant-virus interactions has led to investigation of the effects of their induced expression on virus accumulation and symptomatology (5,6,7). These alterations in defense gene expression might not necessarily provide a line of defense against virus infection but may have adverse effects on host metabolism that contribute to disease symptom development.…”
mentioning
confidence: 99%
“…Accumulation of ROS was also observed during viral compatible interactions (Riedle-Bauer, 2000;Love et al, 2005;Inaba et al, 2011;Manacorda et al, 2013). Moreover, in some plantvirus interactions, necrotic symptoms are associated with an increase of hydrogen peroxide (H 2 O 2 ) production (Inaba et al, 2011;Manacorda et al, 2013). Following this line of evidence, it was observed that a TMV-Cg mutated strain, carrying a truncated version of CgCP, induced reactive oxidative bursts that led to necrotic phenotypes in arabidopsis and tobacco plants (Kurihara and Watanabe, 2004).…”
Section: Rna Interference-mediated Resistancementioning
confidence: 85%
“…Accumulation of ROS in the apoplast/cell wall compartments takes place early after the activation of the hypersensitive response (HR) (Sagi and Fluhr, 2001). Accumulation of ROS was also observed during viral compatible interactions (Riedle-Bauer, 2000;Love et al, 2005;Inaba et al, 2011;Manacorda et al, 2013). Moreover, in some plantvirus interactions, necrotic symptoms are associated with an increase of hydrogen peroxide (H 2 O 2 ) production (Inaba et al, 2011;Manacorda et al, 2013).…”
Section: Rna Interference-mediated Resistancementioning
confidence: 92%